Combined use of intravenous and topical tranexamic acid in patients aged over 70 years old undergoing total hip arthroplasty - Junqing Jia (Journal of Orthopaedic Surgery and Research, 2019)
Abstract Purpose The present study was designed to evaluate the efficacy and safety of combined use of intravenous (IV) TXA administration and topical intraarticular tranexamic acid (TXA) strategy in patients aged over 70 undergoing total hip arthroplasty (THA). Methods One hundred eighty patients were randomized into three groups, including an IV group, a local group, and a combined group. Patients were administrated with 15 mg/kg of IV-TXA in the IV group, 2 g TXA in the topical group, or 15 mg/kg IV-TXA combined with 2 g TXA in the combined group. Total blood loss (TBL), maximum hemoglobin drop, the transfusion rate and the number of allogeneic blood units, and the incidence of deep venous thrombosis (DVT), and pulmonary embolism (PE) were recorded and analyzed. Results TBL was 757.75 ± 188.95 mL in the combined group, which was significantly lower than in the IV group (892.75 ± 218.47) or the topical group (1015.75 ± 288.71) (p = 0.015, p = 0.001 respectively). The mean values of maximum hemoglobin drop in the combined, IV, and topical groups were 2.67 ± 0.42, 3.28 ± 0.52, and 3.75 ± 0.62 g/dL, respectively, with a significant intergroup difference (p < 0.001 for all). PE was not detected within 1 month after the surgery. Asymptomatic DVT was reported in 1 patient of the IV group, and in 2 patients from the combined group, while the difference was not statistically significant. Conclusions Compared to intravenous or topical use of TXA, the combined therapy effectively decreased total blood loss and reduced the transfusion rate, simultaneously possessed the same degree of safety in primary THA patients aged over 70.